Pola konsumsi, konsumsi gula, dan status gizi pada wanita usia 35-55 tahun di Desa Batur, Kecamatan Getasan - Karwur, Ferry Fredy; Prameshwari, Deshinta; Rayanti, Rosiana Eva (Jurnal Gizi Klinik Indonesia, 2023)
Consumption pattern, sugar intake, and nutritional status of women aged 35-55 years in Batur Village, Getasan DistrictBackground: According to the Individual Food Consumption Survey of Central Java Province, residents consume an average of 22.9 grams of food from sugar, syrup, and confectionary groups daily, with sugar alone accounting for 20.2 grams. Sweet foods and beverages like sweet tea, tofu, and tempeh are commonly consumed in Central Java. Objective: The study assesses consumption patterns, sugar intake, and nutritional status (including anthropometric measurements, blood sugar levels, fasting blood sugar levels, uric acid levels, and blood pressure) of native Javanese women aged 35-55 in Batur, Getasan. Method: This quantitative research uses a descriptive approach with a sample of 106 women: 48 from Krangkeng village (lower), 22 from Kalitengah village (middle), and 36 from Tekelan village (upper). Research tools include SQ-FFQ, 24-hour food recall, anthropometric measurements, and biochemical and clinical examinations. Results: Food consumption frequency and quantity are highest in Krangkeng village. The average daily sugar consumption per person across all villages is 21.46±10.19 grams, equivalent to an average household purchase of 3,359.43±1,509.13 grams per month (about 3 kg per month per family). Types of sugar consumed include glucose (106.98±30.64 g/day), fructose (5.64±7.99 g/day), sucrose (102.18±23.75 g/day), and lactose (1.98±8.38 g/day). Average measurements for BMI, blood sugar, fasting blood sugar, uric acid, and blood pressure fall within normal ranges for women of this age group. Conclusion: Krangkeng village shows higher food consumption rates, likely due to more access to food supplies. Average daily sugar consumption remains below recommended levels (25 g/day). Overall, the women surveyed's nutritional status, biochemical, and clinical profiles are generally within normal range.